Repeated administration of subconvulsant doses of GABA antagonist drugs. II. Effect on monoamine-mediated behaviour. - Cowen, P; Nutt, D; Batts, C; Green, A; Heal, D (Springer-Verlag, 1982)
The effect on monoamine-medical behaviour of repeated daily subconvulsive doses of the GABA antagonist drugs pentylenetetrazol (PTZ) (30 mg/kg for 8 days), picrotoxin (5 mg/kg for 4 days) and bicuculline (3.5 mg/kg for 16 days) was investigated. None of the drugs, administered chronically, increased behavioural responses to the 5-hydroxytryptamine agonist quipazine (25 mg/kg), and neither picrotoxin nor bicuculline altered the locomotor response to the dopamine agonist apomorphine (AP) (0.1 mg/kg). By contrast, repeated doses of PTZ increased the locomotor response to AP, and also increased circling responses to both AP (0.5 mg/kg) and methamphetamine (2.0 mg/kg) in unilateral nigrostriatal-lesioned rats.